Fertility rules : the definitive guide to male and female reproductive health - Schrock, Leslie (Simon Element, 2023)
"Leslie Schrock is back with the first preconception guide for both male and female fertility. Based on cutting-edge science, Fertility Rules offers a holistic plan for every age and stage of the process, whether you're planning to conceive or in the throes. Unlike some other fertility books, it also includes practical content tailored to help the mental health of prospective parents"--